The Influence of Local Culture on Customary Practices in Muslim Societies: A Case Study in Central Java - Wijaya Wijaya; Kaito Tanaka; Daiki Nishida; Miku Fujita (Journal of Noesantara Islamic Studies, 2025)
Local culture significantly influences customary practices within Muslim societies, shaping unique expressions of Islamic teachings across diverse regions. In Central Java, Indonesia, traditional practices are deeply intertwined with Islamic values, creating a distinctive cultural-religious identity. While these practices enrich local traditions, they also raise questions about the balance between cultural preservation and religious orthodoxy. This study aims to explore the influence of local culture on customary practices in Central Java’s Muslim communities, examining how cultural elements align with or diverge from Islamic principles. A qualitative case study approach was employed, involving in-depth interviews with community leaders, religious scholars, and practitioners of traditional customs in three rural areas. Observational data and document analysis of local texts and records supplemented the interviews, offering a comprehensive understanding of the interplay between culture and religion. The findings reveal that local culture plays a pivotal role in shaping religious practices, particularly in rites of passage, social ceremonies, and communal worship. These findings highlight the dynamic relationship between religion and culture, emphasizing adaptation and negotiation. The study concludes that cultural sensitivity and context-specific approaches are essential for understanding and preserving the diversity of Islamic expressions.